Serving to win: exploring serve-reception effectiveness in high-level male and female sitting volleyball players - Cavedon, Valentina; Sandri, Marco; Zuccolotto, Paola; Biasiolo, Caterina; Zancanaro, Carlo; Milanese, Chiara (Frontiers in Sports and Active Living, 2024)
Introduction This study was planned to assess the association between serve efficacy and match outcome, and to investigate which factors are associated with serve efficacy in high-level male and female Sitting Volleyball players. Methods The study sample was comprised of a total of 3,664 serving actions, performed during the 2020 Paralympic Games and the 2022 Sitting Volleyball World Championship. For each serving action, we considered serve efficacy (i.e., Point lost, Negative Serve, Positive serve and Point won), serve zone, type of serve technique, target zone of the serve, type of reception, receiving player and match outcome (i.e., match won, or match lost). Results The Mixed-effects logistic regression model showed that serve efficacy is significantly associated with the match outcome, increasing serve efficacy being associated with increased chances of winning the game. The ratio between the probability of winning and losing the game started at 0.86 for a Point lost and increased to 1.67 for a Point won. Compared to Negative serves, Positive serves were associated with a higher probability that the opponent team would use a low reception rather than a high reception. In turn, a low reception was associated with a higher chance (from 45.1% to 58.3%) of the receiving team committing an error in the side-out phase. Discussion Based on these results, it is recommended that high-level coaches focus on improving their players' serve efficacy by instructing them on managing risk, avoiding serves to the front zone, and reducing the likelihood of overhead receptions.